FDI & IDX: A CAUSALITY TEST - Syamni, Ghazali; Rasyidin, M. (JURNAL KEBANGSAAN, 2015)
This study aims to examine the causal relationship between foreign net purchase and stock market capitalization, as well as to examine the effect of foreign direct investments towards the development of stock markets in Indonesia. The data used in this study were secondary data of FDI and market capitalization issued quarterly in the form of time series during the period of January 2000 to September 2010 obtained from the Board of Investment, Bank Indonesia, Central Bureau of Statistics and the Indonesia Stock Exchange. Data were analyzed by using Grangers Causality method to test the causal relationship between the two variables. The predictive power of prior information may indicate a causal relationship between y and z in the long term. The results indicate that there is a pattern of one-way causal relationship between foreign net purchase and market capitalization, which means foreign net purchase significantly, affects market capitalization. The results also found the effect FDI has on market capitalization and this indicates that the Indonesian stock market is getting better. This condition is also supported by the strengthening of Indonesian economy fundamentals that led to foreign investors interested to invest in Indonesia.Â .Keywords : causality, FDI, market capitalization.